Penanggulangan Covid-19 Berbasis Moderasi Beragama di Desa Gomong Sakura, Selaparang Mataram: Covid-19 Management Based on Religious Moderation in Gomong Sakura Village, Selaparang Mataram - Suparmanto Suparmanto; Andi Riski (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
The COVID-19 pandemic has changed many arrangements of human life around the world, especially in terms of education and health, therefore the involvement of UIN Mataram here is to direct its students to carry out Participatory Work Lectures from Home (KKP-DR). The implementation of the KKP-DR is focused on aspects of education and health that are moderated by religion. These two aspects are expected for students to be involved in helping the government overcome various problems in education and health. In Gomong Sakura Village, Selaparang, Mataram. Various efforts were made by students in both aspects. In the field of education, students provide tutoring for school children from elementary school to high school levels, while in the health sector, students carry out socialization to prevent the spread of Covid-19. Pandemi covid 19 telah merubah banyak tatanan kehidupan manusia diseluruh dunia terutama dari segi pendidikaan dan Kesehatan maka dari itu Keterlibatan UIN Mataram di sini adalah mengarahkan mahasiswanya untuk melaksanakan Kuliah Kerja Partisipatif Dari Rumah (KKP-DR). Pelaksanaan KKP-DR difokuskan pada aspek pendidikan dan Kesehatan yang bermoderasi agama. Kedua aspek tersebut diharapkan mahasiswa dapat terlibat untuk membantu pemerintah mengatasi berbagai persoalan dalam pendidikan dan kesehatan. Di Desa Gomong Sakura, Selaparang, Mataram. Berbagai upaya dilakukan oleh mahasiswa pada kedua aspek tersebut. Dalam bidang pendidikan, mahasiswa memberikan bimbingan belajar kepada anak sekolah mulai dari jenjang sekolah dasar hingga sekolah menengah, sedangkan pada bidang kesehatan, mahasiswa melakukan sosialisasi pencegahan penyebaran Covid-19.